Sex-specific recombination patterns predict parent of origin for recurrent genomic disorders - Trenell J. Mosley; H. Richard Johnston; David J. Cutler; Michael E. Zwick; Jennifer G. Mulle (BMC, 2021)
Abstract Background Structural rearrangements of the genome, which generally occur during meiosis and result in large-scale (> 1 kb) copy number variants (CNV; deletions or duplications ≥ 1 kb), underlie genomic disorders. Recurrent pathogenic CNVs harbor similar breakpoints in multiple unrelated individuals and are primarily formed via non-allelic homologous recombination (NAHR). Several pathogenic NAHR-mediated recurrent CNV loci demonstrate biases for parental origin of de novo CNVs. However, the mechanism underlying these biases is not well understood. Methods We performed a systematic, comprehensive literature search to curate parent of origin data for multiple pathogenic CNV loci. Using a regression framework, we assessed the relationship between parental CNV origin and the male to female recombination rate ratio. Results We demonstrate significant association between sex-specific differences in meiotic recombination and parental origin biases at these loci (p = 1.07 × 10-14). Conclusions Our results suggest that parental origin of CNVs is largely influenced by sex-specific recombination rates and highlight the need to consider these differences when investigating mechanisms that cause structural variation.